2009
DOI: 10.4141/cjas09023
|View full text |Cite
|
Sign up to set email alerts
|

Performance and carcass characteristics of steers fed a low acid-detergent lignin hull, high-oil groat oat in growing and finishing diets

Abstract: . 2009. Performance and carcass characteristics of steers fed a low acid-detergent lignin hull, high-oil groat oat in growing and finishing diets. Can. J. Anim. Sci. 89: 521Á530. Two trials were conducted to evaluate the performance and carcass traits of steers fed a low aciddetergent lignin hull, high-oil groat (LLH-HOG) oat in cattle diets. In trial 1, 400 steers (275.4920.8 kg) were fed one of two diets with barley or LLH-HOG oat at 37.8% of the diet (DM basis). Dry matter intake (DMI) was lower (P00.02) (7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 26 publications
0
7
2
Order By: Relevance
“…This is in contrast to the observations of Zalinko et al (2009), who noted that the efficiency of gain for growing calves fed the low lignin hull, high oil groat oat was improved by 7.5% over that of the barley-fed calves. In the current study, replacement of barley with either rolled or whole CDC SO-I oat did not appear to affect the composition of gain as cumulative USFAT and USLDA gain over the 105-d backgrounding period were not different (P 00.21) among dietary treatments (Table 2).…”
contrasting
confidence: 56%
See 2 more Smart Citations
“…This is in contrast to the observations of Zalinko et al (2009), who noted that the efficiency of gain for growing calves fed the low lignin hull, high oil groat oat was improved by 7.5% over that of the barley-fed calves. In the current study, replacement of barley with either rolled or whole CDC SO-I oat did not appear to affect the composition of gain as cumulative USFAT and USLDA gain over the 105-d backgrounding period were not different (P 00.21) among dietary treatments (Table 2).…”
contrasting
confidence: 56%
“…In contrast, Zalinko et al (2009) found that calves fed a rolled oat diet had lower DMI relative to barley-fed calves. These authors hypothesized that the fat content of the oat diet relative to rolled barley diet (5.9 vs. 3.0%) was a contributing factor to the reduced DMI.…”
contrasting
confidence: 39%
See 1 more Smart Citation
“…This negative effect on ADG during the adaptation period could potentially be reduced by increasing the time of the dietary adaptation period to the high-grain diet for cattle fed barley-based diets. However, research has also shown improved ADG in steers fed barley-based diets than cornor oat-based diets over the first 56 d on feed (Zalinko et al 2009). It is not clear as to the reasons for discrepancies between studies, but it could be because of a number of other factors including cattle age, genetics, other dietary ingredients, and environment.…”
Section: Discussionmentioning
confidence: 99%
“…This negative effect on ADG during the adaptation period could potentially be reduced by increasing the time of the dietary adaptation period to the high-grain diet for cattle fed barley-based diets. However, research has also shown improved ADG in steers fed barleybased diets than corn-or oat-based diets over the first 56 days on feed (Zalinko et al 2009). It is not clear as to the reasons for discrepancies between studies, but it could be because of a number of other factors including cattle age, genetics, other dietary ingredients, environment, etc.…”
Section: Resultsmentioning
confidence: 99%